Cobalt-substituted SrTi0.3Fe0.7O3-: δ a stable high-performance oxygen electrode material for intermediate-temperature solid oxide electrochemical cells - Zhang, Shan-Lin (2018)
A key need in the development of solid oxide cells (SOCs) is for electrodes that promote fast oxygen reduction and oxygen evolution reactions at reduced operating temperature (≤700 °C), with sufficient durability to allow operation over desired 40 000 h lifetimes. A wide range of electrode materials have been investigated, with some providing resistance low enough for cell operation below 700 °C, but it is generally found that the electrode performance degrades over time. Here we demonstrate an oxygen electrode material, Sr(Ti0.3Fe0.7-xCox)O3-δ (STFC), that provides a unique combination of excellent oxygen electrode performance and long-term stability. The addition of a relatively small amount of Co to Sr(Ti0.3Fe0.7)O3-δ, e.g., x = 0.07, reduces the electrode polarization resistance by >2 times. The STFC electrode yields stable performance in both fuel cell and electrolysis modes at 1 A cm-2. The fundamental oxygen diffusion and surface exchange coefficients of STFC are determined, and shown to be substantially better than those of La0.6Sr0.4Co0.2Fe0.8O3-δ, the most widely used SOC oxygen electrode material. While other electrode materials have been shown to exhibit better oxygen transport coefficients than STFC, they do not match its stability.